Knowledge and Attitudes of Nursing Students Who Have Been Training in Giresun University Faculty of Health Sciences About Brain Death and Organ Donation - Aktaş, Yeşim Yaman; Karabulut, Neziha (Fırat University, 2012)
Objective: This study was carried out as a descriptive study in order to determine knowledge and attitudes of nursing students who have been training in Giresun University Faculty of Health Sciences about brain death and organ donation. Materials and Methods: 150 students studying in Giresun University Faculty of Health Sciences and agreeing to participate in the research were included. In data collection, the questionnare which included 27 items was used. The data were evaluated through percentage distribution. Results: The mean age of nursing students was 20.89 ±1.58 and 86% were female. It was marked that 65.3% of the students do not have information about brain death and organ donation during their study. 66.7% of the students indicated that they wanted to donate all of their tissue and organ, but only 3.3% of them donated their organs. Conclusion: It was determined that the nursing students were not informed about brain death and organ donation sufficiently during the undergradua-te education and the willingness of the nursing students for organ donation was higher whereas the rate of those who actually accepted to donate their organs was low.

Amaç: Bu çalışma, Giresun Üniversitesi Sağlık Bilimleri Fakültesi'nde öğrenim gören hemşirelik öğrencilerinin beyin ölümü ve organ bağışına ilişkin bilgi ve tutumlarını belirlemek amacıyla tanımlayıcı olarak yapılmıştır. Gereç ve Yöntem: Giresun Üniversitesi Sağlık Bilimleri Fakültesi'nde öğrenim gören ve araştırmaya katılmayı kabul eden 150 öğrenci araştırma kapsamına alınmıştır. Verilerin toplanmasında konuya ilişkin 27 soru içeren anket formu kullanılmıştır. Veriler yüzdelik hesaplamayla değerlendirilmiştir. Bulgular: Araştırmaya katılan öğrencilerin yaş ortalaması 20.89±1.58 olup, %86'sı kızdır. Çalışmaya alınan öğrencilerin %65.3'ü öğrenimleri süresince derslerinde beyin ölümü ve organ nakline ilişkin bilgi almadıkları saptanmıştır. Hemşirelik öğrencilerinin %66.7'si doku ve organlarının tümünü bağışlamak isterken, ancak %3.3'ü organ bağışında bulunduğunu belirtmiştir. Sonuç: Hemşirelik öğrencilerinin lisans eğitiminde beyin ölümü ve organ bağışı konusunda yeterince bilgilendirilmedikleri, organ bağışı konusundaki istekliliklerinin yüksek olduğu görülmesine rağmen, organ bağışında bulunan hemşirelik öğrencilerinin çok düşük düzeyde olduğu saptanmıştır.
Giresun Üniversitesi Sağlık Bilimleri Fakültesindeki Hemşirelik Öğrencilerinin Beyin Ölümü ve Organ Bağışına İlişkin Bilgi ve Tutumları